2020
DOI: 10.1609/aaai.v34i08.7042
|View full text |Cite
|
Sign up to set email alerts
|

A System for Medical Information Extraction and Verification from Unstructured Text

Abstract: A wealth of medical knowledge has been encoded in terminologies like SNOMED CT, NCI, FMA, and more. However, these resources are usually lacking information like relations between diseases, symptoms, and risk factors preventing their use in diagnostic or other decision making applications. In this paper we present a pipeline for extracting such information from unstructured text and enriching medical knowledge bases. Our approach uses Semantic Role Labelling and is unsupervised. We show how we dealt with sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…TransE [23] is a well-known translational approach that uses simple assumptions to achieve considerably accurate and scalable results, proved to be effective and efficient embedding model [24]. Several enhanced models (e.g.…”
Section: Knowledge Embedding Representationmentioning
confidence: 99%
“…TransE [23] is a well-known translational approach that uses simple assumptions to achieve considerably accurate and scalable results, proved to be effective and efficient embedding model [24]. Several enhanced models (e.g.…”
Section: Knowledge Embedding Representationmentioning
confidence: 99%
“…Several empirical studies that have been conducted recently have revealed difficulties in processing and acquiring new knowledge from unstructured text [12][13][14][15]. This is especially evident from groupware discussions, considering the nature of conversations which are not written in formal sentence patterns and contain grammatical and typographical errors.…”
Section: Introductionmentioning
confidence: 99%